Overview Of The Student Satisfaction Level Of The Penjaskesrek FKIP Undana Study Program In Using E-Learning During The Covid-19 Pandemic - Ronald Dwi Ardian Fufu; Erwin S Neolaka; Yudabbirul Arif; Al Ihzan Tajuddin; Michael Johannes Hadiwijaya Louk (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
In learning the meaning of motion and its application will be different, of course the consequence is injury. This problem is a description of the problems that occur in the Physical Education Study Program. This can affect the level of student satisfaction in using e-learning at Nusa Cendana University at the study program level. The research method used is a qualitative research method with the type of survey research with a research time of 4 months. Students of the physical education health and recreation study program consisting of semester 2 to semester 8, where the delegates for each class are 20 people with a total of 80 people. With data collection techniques using observation, questionnaires and documentation. The results of the study can be concluded that the implementation of online lectures during the covid-19 pandemic is the best solution. the calculation of the average value is known that the aspects of comfort, aspects of relationships and competence are in the satisfied category. On the other hand, there is one aspect that is found to be slightly different from other aspects, namely the cost aspect, this aspect is in the less satisfied category. Overall it can be concluded that the Satisfaction Level of Students of the Physical Education Study Program FKIP Nusa Cendana University in Using E-Learning During the Covid-19 Pandemic is in the satisfied category.